2010
DOI: 10.1371/journal.pone.0009196
|View full text |Cite
|
Sign up to set email alerts
|

Growing Burkholderia pseudomallei in Biofilm Stimulating Conditions Significantly Induces Antimicrobial Resistance

Abstract: Background Burkholderia pseudomallei, a Gram-negative bacterium that causes melioidosis, was reported to produce biofilm. As the disease causes high relapse rate when compared to other bacterial infections, it therefore might be due to the reactivation of the biofilm forming bacteria which also provided resistance to antimicrobial agents. However, the mechanism on how biofilm can provide tolerance to antimicrobials is still unclear.Methodology/Principal FindingsThe change in resistance of B. pseudomallei to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 45 publications
5
86
0
2
Order By: Relevance
“…22 We speculate that bacillary emboli (Figure 2c) or smaller clusters may be held together and protected against antibiotics and host immune response by a surrounding biofilm, a well-known phenomenon in B. pseudomallei infection. 23 Bone marrow infection, shown in one of our cases (case 5, Table 2), is consistent with bone marrow inflammation found in another series, 24,25 and the observation that bacteria could be cultured from bone marrow. 26 Morphologically intact bacteria were demonstrated in the wall of the mycotic aneurysm confirming B pseudomallei infection (case 7, Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…22 We speculate that bacillary emboli (Figure 2c) or smaller clusters may be held together and protected against antibiotics and host immune response by a surrounding biofilm, a well-known phenomenon in B. pseudomallei infection. 23 Bone marrow infection, shown in one of our cases (case 5, Table 2), is consistent with bone marrow inflammation found in another series, 24,25 and the observation that bacteria could be cultured from bone marrow. 26 Morphologically intact bacteria were demonstrated in the wall of the mycotic aneurysm confirming B pseudomallei infection (case 7, Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…[10][11][12]35,[38][39][40] Even strains that originate from the same parental strain exhibit phenotypic diversity, particularly in colony morphology. 17,41 Both arginine deiminase and quorum sensing systems have been suggested to modulate the formation of colonies in response to different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…9 The general virulence determinants, such as extracellular enzymes (protease, phospholipase, and catalase), biofilm formation, swarming ability, and lipopolysaccharide (LPS) types of different B. pseudomallei isolates are diverse. [10][11][12] The expression of one or more of these virulence determinants is associated with changes in bacterial colony morphology. [13][14][15][16] In B. pseudomallei, wrinkled and dry colonies are commonly observed in human isolates, and these morphologies are associated with the degree of virulence in BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%
“…The very high minimum biofilm eliminating concentration explains the lack of success in the treatment of chronic manifestations of B. pseudomallei infection. In addition, the biofilm mutant strains are resistant to all antimicrobial agents when induced to form biofilm [26].…”
Section: Antimicrobial Agents and B Pseudomalleimentioning
confidence: 99%
“…The possible drug-resistant mechanism of biofilm is still unclear. However, research found that stimulation of the bacteria to produce biofilm results in upregulation of some genes to be resistant against antimicrobial agents [26]. The protein expression study in B. pseudomallei wild-type and biofilm defective mutants in biofilm stimulating conditions, revealed a different protein expression under biofilm stimulating conditions.…”
Section: Antimicrobial Agents and B Pseudomalleimentioning
confidence: 99%